Interrogating the Contestations in Zimbabwe’s New Marriage Law and Arbitration in Family Disputes - Bernard Pindukai Humbe; Fortune Sibanda (E-Journal of Religious and Theological Studies)
This study focuses on the new Marriages Act and arbitration in family disputes among the Shona people of Zimbabwe, who happen to be the largest ethnic group constituting about 75% of the Zimbabwean population. The problem identified by this study was that the new Act has been received with mixed emotions especially by religious communities with the majority complaining that it promotes promiscuity and marriage breakups. Using Alternative Dispute Resolution as a conceptual framework and in-depth interviews, observation and documentary analysis of print and electronic media to gather data, the study established that the new Act promotes paradoxes over marriage dispute resolution because the customary law and decisions have been submerged. The research concludes that the new Marriages Act is an ambivalent legal framework that requires continual interrogation among different stakeholders for sustainable marriage unions in Zimbabwe. The study recommends the harmonisation between the law and societal culture on marriage to ensure an effective and contextual family arbitration mechanism. The research bridges the knowledge gaps in scholarship on the impact of Zimbabwe’s legal reforms on gender relations catapulted by the tensions between statutory law and customary law encountered in the process of harmonising traditional and modern views on marriage and family structures in post-colonial contexts, which were historically influenced by patriarchy.